Coagulating Potential of Fresh Cow Milk from Dairy Cattle in Ghana and the Economic Value of Processing Cheese - Aboagye, C.W. (University of Ghana, 2018)
Milk is a nutritious food obtained from ruminants such as cattle, goats and sheep. In Ghana, milk is usually obtained from indigenous cattle. These have low milk yield hence the introduction of hybrids and exotic breeds. Embracing these new breeds has to an extent increased milk yield. The problem is that the yield is still not enough. Also, the milk obtained is usually sold in the fresh state which goes bad within a short time and is also patronized by few Ghanaians. For these reasons it is necessary to add value to fresh milk and one way of doing this is by processing cheese. This would provide farmers with some economic benefit and also bring more variety in processed milk products in the country. Milks were collected from three different cattle breeds; White Fulani, Jersey and a Cross breed. Physicochemical analyses were done on the milks to compare them. After which each of the milks was coagulated with five different coagulants (Sodom apple, rennet, acid, Sodom apple + acid and rennet + acid) to ascertain their coagulating potential and physicochemical properties. Then, the milks were pooled and coagulated using the different coagulants to observe their cheesing characteristics and protein profile. Finally, economic analysis was done on the different cheeses to find out if it was viable to commercially produce cheese in Ghana. One-way ANOVA was used to determine if differences existed amongst the milks from the breeds and the cheeses made from the different coagulants. Two-way ANOVA was used to determine the interaction between the breeds and coagulants for the various indices measured for the coagulum obtained. It was observed that the physicochemical properties of the milks from the breeds were similar in fat and protein content. Milk from the White Fulani took the shortest time to coagulate and milks coagulated with Acid first had the least coagulation time. The highest coagulum yield was obtained from milk processed with Sodom apple and milk from the Jersey cow. Coagulum made with Acid had the highest meltability and coagulum from Sodom apple was highest for 7 out of 10 sensory attributes. Amongst all the coagulum, the ones processed from Rennet + acid and Sodom apple + acid had the hardest texture with cheese from Sodom apple being the softest. For the protein profile, Rennet only had all the caseins being hydrolysed. Acid only and Sodom apple + acid showed similar results. All three caseins were not hydrolysed. The economic analysis showed that the cheeses if processed commercially can be sold at the following prices: Rennet only - GHȻ 8.00, Acid only - GHȻ 16.00, Sodom apple only - GHȻ 6.00, Sodom apple +acid - GHȻ 12.00 and Rennet +acid - GHȻ10.00. Cheese can be obtained from the breeds analyzed using different coagulants and it would be viable and profitable to produce cheese commercially in Ghana.
MPhil.
Keywords: Fresh Cow Milk; Dairy Cattle; Cheese